Ultrasonic chemical sensor for detection of aliphatic and aromatic hydrocarbons in air - Balcerzak, Andrzej; Zhavnerko, Genady (Archives of Acoustics, 2007)
The reaction of the organic monomolecular Langmuir–Blodgett layer, deposited on thesensor delay line using surface acoustic wave, on the presence of vapors of some aliphatic andaromatic hydrocarbons in air has been investigated. The chemical composition of this layer isan equimolar mixture of 5-[[1,3-dioxo-3- [4- (1-oxooctadecyl) phenyl] propyl] amino] – 1,3– benzenedicarboxylic acid (DA) and cetylamine (CA). Time of sensor reaction is less than2 seconds. Decrease of the differential frequency after contact with the vapor-air mixture anddecrease of this frequency in time are different for various hydrocarbons; a length of the chainis important for aliphatic hydrocarbons and a presence or not of side chains – for aromaticones. The reaction of the sensor on the hydrocarbon vapors in air is reversible.